Sleep in marathon and ultramarathon runners: a brief narrative review - Nikolaidis, Pantelis T.; Weiss, Katja; Knechtle, Beat; Trakada, Georgia (Frontiers in Neurology, 2023)
Introduction Sleep is considered a fundamental biological function in humans necessary for recovery from daily physical activities. Considering the increasing popularity of long-distance running and participation in races such as marathons and ultramarathons, the aim of the present study was to review the relationship of such strenuous physical activities with sleep. Methods A search of Scopus was performed on 24/6/2023 using the syntax [ABS (sleep) AND ABS (marathon)] to identify relevant papers, the references of which were hand-searched to find additional sources. Results Optimal sleep has been shown to affect injury prevention and susceptibility to infection positively. In turn, participation in a marathon race may influence nocturnal autonomic modulation and disturb homeostasis. Ultramarathon races may have such a long duration that results in sleep deprivation even for several days, where sleep duration is quite below the physiological range. It seems that for ultramarathons of short duration, continuous running and sleep deprivation are beneficial for performance. In contrast, for races longer than 200 miles, it is necessary to develop sleep strategies to sustain performance. Conclusion In summary, the longer the distance of a running race, the greater the importance of an optimal sleep for race performance as well as the impact of a race on sleep.